Migration, health, and development - Lahiri, Subrata; Paswan, B.; Das, K. C. (Rawat Publications, 2011)
Selected papers on population, internal migration, and reproductive health of the population presented at the International Conference on Emerging Population Issues in the Asia-Pacific Region: Challenges for the 21st Century on 10-13, December, 2006 at International Institute for Population Sciences, Mumbai.